Glossary of words, phrases and sentences in Quechua-Spanish frequently used in physical education - Rojas-Tello, Luis L. (2022)
In Peru there are 48 languages ​​with different degrees of use and domain according to the linguistic needs of each community. In Ayacucho, one of its 24 departments, the Quechua language stands out due to the increase in its use in recent years, even in the academic spaces of higher undergraduate and graduate studies. The objective of this article is to build a glossary of words, phrases and sentences in Quechua and Spanish frequently used in Physical Education; based on the identification of nouns, adjectives, verbs and adverbs. From the basic methodology of analytical descriptive character and non-experimental design, the glossary of words was achieved. The results indicate that the most used Quechua words in Physical Education are adverbs, followed by verbs, adjectives and, to a lesser extent, nouns.